Effects of vortex finder length on flow field and collection efficiency of cyclone in an industrial‐scale circulating fluidized bed boiler: Numerical study. (28th April 2020) - Hwang, In Sik; Jeong, Hyo Jae; Hwang, Jungho
Summary: Cyclone separators are key components of circulating fluidized bed (CFB) boilers. The factors that can affect the cyclone performance include body diameter, total height of the cyclone, and diameter and length of the vortex finder (VF). In this study, the effect of the VF length on the cyclone performance in a 340‐MWe CFB boiler operated by Korea South‐East Power Corporation was analyzed using computational fluid dynamics. A dense discrete phase model with kinetic theory of granular flow approach was employed for modeling the interactions of sand with a gas phase. As the VF length decreased, the unexpected short‐circuit flow around the VF reduced the pressure difference between the center and the cyclone wall. This reduced the swirl intensity, decreasing the natural vortex length. As the VF length increased, the short‐circuit flow decreased, along with the pressure difference and swirl intensity, reducing the natural vortex length. Thus, increasing the VF length beyond a certain value is not recommended, and there is an optimum VF length for maximizing the cyclone collection efficiency. Abstract :